Torch bottle / Muhammad Shazwan Puzi ... [et al.] - Puzi, Muhammad Shazwan; Suzaini, Farzana Suaidah; Mohd Khairul Anuar, Nurul Aina Balqis; Mohd Zaidi, Nur Murniza (2021)
A torch bottle is a product that combines a torchlight and a bottle, which makes it easy for people to carry both items at a time. Since the Covid-19 pandemic, it has become a trend for people to do recreational activities such as jungle trekking, hiking, night walk, night patrol, and camping. Torch Bottle is specially designed for those people who like to do recreational activities. The objective of this torch bottle is to make it easier for people who want to bring a water bottle and torchlight at the same time especially adventurous hikers who love taking night walks in the jungle, and patrol guards to use during their night patrol. The function of the product is to help consumers to see better at night while still allowing them to drink water from the bottle. The torch bottle can be used by four different age group generations such as Baby Boomers, Generation X, Millennial, and Generation Z. The product is designed in a cylinder shape with a portable torchlight under the bottle. The novelty of this product is the torchlight can be removed when the bottle is washed. Besides, the torchlight from the bottle can be turned on using batteries or a thin-film solar panel. Thus, the product is sustainable because it saves energy by using solar panels. It is also coated with stainless steel which makes it environmentally friendly, durable, safe, and corrosion-resistant. This innovation is a great way of reducing the cost of the product since the production cost of the two products which are water bottles and torchlight is higher.